2012
DOI: 10.1159/000338858
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Experience of Psoriasis in the Genital Area

Abstract: Background: Psoriasis in the genital area is often neglected, although it bothers a substantial number of patients. Objective: To study both the role of the physician in the treatment of genital psoriasis and the symptom intensity of these lesions as experienced by the patients. Methods: A detailed self-administered questionnaire (containing items on the role of the physician and genital symptom intensity, range 0–10) was filled in by members of the Dutch Psoriasis Society. Results: Data of 277 patients with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 42 publications
3
43
0
6
Order By: Relevance
“…Patients with genital psoriasis experience decreased frequency of intercourse, avoid sexual relationships, and have reduced sexual desire 7,2527. These patients are less comfortable with their own nudity, dating, and intimacy compared with patients with psoriasis lesions on nonsensitive areas of their body 18.…”
Section: Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with genital psoriasis experience decreased frequency of intercourse, avoid sexual relationships, and have reduced sexual desire 7,2527. These patients are less comfortable with their own nudity, dating, and intimacy compared with patients with psoriasis lesions on nonsensitive areas of their body 18.…”
Section: Symptomsmentioning
confidence: 99%
“…Patients experience pain during intercourse or worsening of symptoms after intercourse as well 25. Women in particular experience dyspareunia and are distressed by the impact of genital psoriasis on sexual function compared with men 7,28. However, this distress improves with treatment targeted toward the genital lesions 28.…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study done in South Korea in patients with adult-onset psoriasis (aged 60 years and older) found that 75 % of patients suffered from chronic itch and 35 % suffered from moderate to severe itch that interrupted normal daily activities [73]. It is also necessary to evaluate the genital area in patients with psoriasis because of the high prevalence of genital itch in this population [75].…”
Section: Cutaneous Conditionsmentioning
confidence: 99%
“…Most patients with genital psoriasis experience localised mild to moderate sensory skin symptoms such as itch, pain and/or burning (7)(8)(9)(10). Diagnosis of genital psoriasis can usually be made on the basis of its typical clinical appearance that includes symmetrical, welldemarcated, brightly erythematous thin plaques that usually lack the typical dry scaling (11).…”
mentioning
confidence: 99%